ANALISIS STRATEGI PERENCANAAN PEMERINTAH DAERAH DALAM PEMUNGUTAN PAJAK DAERAH DENGAN SISTEM ONLINE KABUPATENSIDENRENG RAPPANG - T, Ruslang; Nur, Muhammad; Hasrullah, Hasrullah (Cateris Paribus Journal, 2022)
Abstract This study aims to find out more clearly about the local government's strategy in planning local tax collection by means of an online system in Sidenreng Rappang Regency. The data collection techniques used in this study were interviews, observation, and documentation. The subjects in this study were research samples, namely the Regional Revenue Agency (BAPENDA) of Sidenreng Rappang Regency. This study uses a qualitative descriptive analysis. After going through the analysis process, the results of this study can be concluded that, Local Tax Collection with the Online System in Sidenreng Rappang Regency is based on the legal basis of the Sidenreng Rappang Regent Regulation Number 20 of 2019, and there is still a lack of awareness of taxpayers in paying taxes. In the regent's regulation regarding the Online Local Tax and Retribution System, only 3 types of taxes are regulated in it, namely hotel tax, restaurant tax and entertainment tax. In implementing the online system, the Sidenreng Rappang Regency Government collaborated with Bank SULSELBAR as the operational executor, and submitted an integrated retail payment service via electronic network to the Regional Revenue Agency. Due to limited tools, the Regional Revenue Agency of Sidenreng Rappang Regency is temporarily focusing on installing an online tax collection tool for restaurant taxes.